Sustainable mobility for urban regeneration - Ilenia Spadaro; Chiara Rotelli; Pietro Adinolfi (TeMA: Journal of Land Use, Mobility and Environment, 2023)
The choice of the mobility system is very topical today because it determines how the territories will develop in the years to come, which infrastructures will have to be built and which lifestyles will take shape in the cities of the future. The research presented in the paper starts from the study of sustainable mobility and the analysis of virtuous cases. From this study, a methodological approach was defined which identifies the main phases to follow and the aspects to pay attention in order to achieve a sustainable regeneration of the territory starting from the proposition of sustainable mobility projects. This approach also proposes a method and instrument for assessing the level of sustainability in line with the principle “Do No Significant Harm” presented in the National Recovery and Resilience Plan. The priorities aspect introduced concerns the integration of the quadruple helix concept, for a multi-stakeholder governance and sustainable regeneration. The illustrated research involves in fact four actors: it starts from a call for proposals carried out within the Genoa University, promoted by the Municipality of Albisola Superiore, in Liguria region, and sees the collaboration of the R2M Solution company and citizens.